AB0896 REINFECTION OF PROSTHETIC JOINT WITH A DIFFERENT MICROORGANISM: A PROSPECTIVE COHORT STUDY. (June 2019) - Beal, Caroline; Zeller, Valerie; Keroumi, Younes; Meyssonnier, Vanina; Heym, Beate; Chazerain, Pascal; Marmor, Simon
Abstract : Background: Treatment failure of prosthetic joint infection (PJI) may be due to relapsing infection (with the same microorganism) or a new infection (with a different microorganism). Data on new prosthetic joint infections (NPJI) are scarce, although they represent a devastating complication and a therapeutic challenge of joint arthroplasty. Objectives: The aim of this study was to describe epidemiological, clinical and microbiological characteristics of NPJI, their treatment and outcome. Methods: This observational single-center cohort study was conducted in a French referral center for bone and joint infections. All patients admitted between January 2000 and December 2015 with a documented hip or knee PJIs and at least 2 years of follow-up, were identified. Among those, all patients treated in our center for at least two successive PJIs, involving the same joint and due to different microorganisms, were included. We compared these patients with a random selection of 124 "single"-PJIs (72 knee and 52 hip prostheses) treated in our center and followed at least 2 years. Results: Among 909 PJIs treated during the study period, 62 patients with 70 NPJIs were included (7.7%) NPJIs developed more frequently in knee (15.7%) than in hip prostheses (4.4%) (p<0.001). Median [range] age was 70 [66-80] years old and median [range] body mass index was 28.7 [25-33] kg/m 2 . Median [range] duration from the first to the NPJI was 16 months [0-98]. Hematogenous spread of the infection was quite higher in NPJIs compared to single-PJIs (92% versus 31% (p=0.0001). NPJIs were predominantly monomicrobial (82%), due to S. aureus (29%), Streptococcus sp. (29%) Gram-negative bacilli (11%) or others (31%). A curative strategy was applied to 71% of the patients with a NPJI: DAIR (31%), 1-stage exchange arthroplasty (24%), 2-stage exchange arthroplasty (5%) and other strategies (11%). For the other patients, prolonged suppressive antibiotic therapy was prescribed (29%), combined with surgery in 10% of patients. Eight patients had a second NPJI, 6 were an acute hematogenous PJI. Four risk factors for NPJI were identified by multivariate analysis : chronic dermatitis (odds ratio [OR] 11.49; 95% CI, 2.40, 55.01; p=0.002), 2-stage exchange arthroplasty during the first PJI (OR 6.99; 95% CI, 2.83, 17.27; p=0.0001), high blood pressure (OR 3.17; 95% CI, 1.39, 7.20; p=0.006) and male gender (OR 2.99;95% CI, 1.35, 6.60; p=0.007). Conclusion: NPJIs are complex PJI affecting more frequently the knee prostheses. They occur predominantly via hematogenous spread from a distant infectious focus, especially the skin. In these complex settings, management by multi-disciplinary teams, should be adapted to each clinical situation. Disclosure of Interests: None declared